Relationship between parental autonomy support and academic motivation among junior high students - Syipa Husni Fadilah; Afra Hafny Noer; Surya Cahyadi; Laila Qodariah; Langgersari Elsari Novianti (Program Studi bimbingan Konseling PPs UNM Makassar, 2019)
This study aims to observe the relationship between parental autonomy support and academic motivation among junior high students. This correlational study collected data from 124 students and their mothers. Convenience sampling was used. The instruments employed were Perceived Parental Autonomy Support Scale and Academic Self-Regulation Questionnaire translated into Indonesian. The Spearman’s Rank was used for correlation analysis. The results revealed that parental autonomy support and maternal autonomy support has a positive correlation with students’ autonomous motivation. The more frequently students receive support from parents and the more frequently mothers give support to their children, the higher motivation students have to perform activities they desire. Maternal autonomy support also associates positively with students’ controlled motivation. The more often mothers give freedom, the higher motivation students have to do activities coming from internal and external pressures. Parental control perceived by students and maternal control have no link with overall motivation.